2010
DOI: 10.1090/s0002-9939-2010-10771-2
|View full text |Cite
|
Sign up to set email alerts
|

Congruences via modular forms

Abstract: Abstract. We prove two congruences for the coefficients of power series expansions in t of modular forms where t is a modular function. As a result, we settle two recent conjectures of Chan, Cooper and Sica. Additionally, we provide tables of congruences for numbers which appear in similar power series expansions and in the study of integral solutions of Apéry-like differential equations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…Many authors have subsequently studied arithmetic properties of B(n) ′ s and discovered similar three term congruence relations for other Apery like numbers. For related work see [1,3,6,7,10,11].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Many authors have subsequently studied arithmetic properties of B(n) ′ s and discovered similar three term congruence relations for other Apery like numbers. For related work see [1,3,6,7,10,11].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In our theorems, we have only examined modular forms on genus zero Γ 0 (N ). However, many examples exist for modular forms on subgroups of higher genus (see [6,11]). An infinite family of examples on a subgroup of higher genus would be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Our result was proved by Jarvis and Verrill in the case where the sum begins with n = 1 in (3.2). In [6] it is mentioned that Stienstra has indicated that the result follows in the case where n = 0 by formal group theory. We give a proof here for completeness.…”
Section: Preliminariesmentioning
confidence: 98%
“…(k + 1) 2 C(n; k + 1), (28) with C(n; k) as in (27). For the second congruence, we used the presence of the term [mn 1 ] q [mn 3 ] q , which is divisible by Φ m (q) 2 , together with…”
Section: Proof We Havementioning
confidence: 99%
“…A major motivation for this paper is the observation of R. Osburn and B. Sahu [28] that all Apéry-like numbers appear to satisfy supercongruences. However, despite recent progress [29], it remains open to show that, for instance, the Almkvist-Zudilin numbers [4, sequence (4.12) (δ)], [11], [10]…”
Section: Outlook and Open Problemsmentioning
confidence: 99%